Engineering distributed software a structural discipline. - Kramer, Jeff (Software engineering notes.)
The role of structure in specifying, designing, analysing, constructing and evolving software has been the central theme of our research in Distributed Software Engineering. This structural discipline dictates formalisms and techniques that are compositional, components that are context independent and systems that can be constructed and evolved incrementally. This extended abstract overviews our development of a structural approach to engineering distributed software and gives indications of our future work which moves from explicit to implicit structural specification. With the benefit of hindsight we attempt to give a "rational history" to our research.